Travellers Belgium. - MacDonald, George, ....- (Peterborough, UK : Thomas Cook, 2005)
Background Introduction, The land, History, Governance, Culture, Festivals First steps What to see Brussels, Flanders, Wallonia Getting away Directory Shopping, Entertainment, Children, Sport and Leisure, Food and Drink, Hotels and Accommodation, On business, Practical guide Index
Keywords: België -- Reisgidsen